حضور اکرمﷺپر جادو کے بارے میں غلام احمد پرویز کی آراء کا تنقیدی جائزہ: A CRITICAL REVIEW OF GHULAM AHMED PARVEZ’S VIEWS ABOUT THE MAGIC ON THE HOLY PROPHET (PEACE BE UPON HIM) (Contemporary Journal of Social Science Review, 2025)
Ghulam Ahmed Parvez, opined that a prophet is absolutely immune to the effect of magic, where as it is contrary to what the Holy Quran says. Ghulam Ahmed Parvez refutes the Holy Prophet (SAW) to be bewitched, while it has been described in the authentic traditions (Hadith and Sunnah). In the Holy Quran, we see the disbelievers, blaming the Holy Prophet Muhammad (SAW) as a bewitched person. Ghulam Ahmed Parvez opines that such traditions (Hadith and Sunnah), support the blame of Arabian Pagans. Therefore they are not worthy of being accepted. The reality is that the blame of Pagans relates to the context, other than the context, which is described in traditions. Both the context have been explained explicitly to eradicate the doubts, put forward by Ghulam Ahmed Parvez.